OP0323 INCIDENCE OF CLINICAL FRAGILITY FRACTURES IN POSTMENOPAUSAL WOMEN WITH RHEUMATOID ARTHRITIS. A MULTICENTRIC CASE-CONTROL STUDY. (2nd June 2020) - Gómez Vaquero, C.; Olmos, J. M.; Hernández, J. L.; Cerda, D.; Hidalgo, C.; Martínez López, J.; Arboleya Rodríguez, L. M.; Aguilar del Rey, J.; Martinez Pardo, S.; Ros, I.; Surís, X.; Grados Canovas, D.; et al.
Abstract : Background: Incidence of clinical fractures in rheumatoid arthritis (RA) is not as well-known as hip or vertebral fracture incidence. Objectives: 1. To estimate the incidence of clinical fragility fractures in a population of postmenopausal women diagnosed with RA and compare it with that of the general population; 2. To analyze the risk factors for fracture. Methods: 330 postmenopausal women with RA from 19 Spanish Rheumatology Departments, randomly selected from the registry of RA patients in each center. The control group consisted of 660 Spanish postmenopausal women from the Camargo Cohort. Clinical fractures during the previous 5 years were recorded. Assessed risk factors for fracture were: sociodemographic characteristics, BMD and variables related to RA. Results: Median age of RA patients was 64 yrs. vs. 63 yrs. in controls (ns). Evolution of the disease was 8 yrs. 78% and 76% had RF and ACPA+, respectively. 69% of patients were in remission or low activity. 85% had received glucocorticoids and methotrexate and 40% at least one biological DMARD. We identified 105 fractures (87 fragility and 18 traumatic) in 75 patients. Fifty-four patients and 47 controls had at least one major fracture (MF) (p< 0.001). Incidence of MF was 3.55 per 100 patient-year in patients and 0.72 in controls. Risk factors for MF in RA patients were age, previous fracture, parental hip fracture, postmenopausal period, hip BMD and cumulative dose of glucocorticoids. In controls, risk factors were age, age at menopause and lumbar BMD. Among RA-associated factors, MFs were associated with erosions, disease activity and disability. Previous fracture in RA patients was a strong risk for MF (HR: 10.37 [95% CI: 2.95-36.41]). Conclusion: Between 3 and 4 of every 100 postmenopausal women with RA have a major fracture per year, four times more than the general population. Disease activity and disability associated with RA, the cumulative dose of glucocorticoids and mainly previous fracture are associated with the development of fragility fractures. References: None Acknowledgments: Funded in part by ISCIII (PI18/00762) that included FEDER funds from the EU. Disclosure of Interests: Carmen Gómez Vaquero: None declared, Jose Manuel Olmos: None declared, J. Luis Hernández: None declared, Dacia Cerda: None declared, Cristina Hidalgo: None declared, JA Martínez López: None declared, Luis Marcelino Arboleya Rodríguez: None declared, Javier Aguilar del Rey: None declared, Silvia Martinez Pardo: None declared, Inmaculada Ros: None declared, Xavier Surís: None declared, Dolors Grados Canovas: None declared, Chesús Beltrán Audera: None declared, Evelyn Suero-Rosario: None declared, Inmaculada Gómez Gracia: None declared, Asunción Salmoral: None declared, Irene Martín-Esteve: None declared, Helena Florez: None declared, Antonio Naranjo Grant/research support from: amgen, Consultant of: UCB, Speakers bureau: AMGEN, Santos Castañeda: None declared, Soledad Ojeda Speakers bureau: AMGEN, LILLY, GEBRO, S García Carazo: None declared, Alberto García-Vadillo: None declared, Laura López Vives: None declared, À Martínez-Ferrer: None declared, Helena Borrell Paños: None declared, Pilar Aguado: None declared, Raul Castellanos-Moreira: None declared, Cristian Tebé: None declared, Núria Guañabens: None declared